Multimedia Simulation Model on Basic Electricial and Electronics Subjects for Vocational Secondary School - Ningrum, Aria Setia; Muslim, Suyitno; Siregar, Eveline (Journal of Education Reseach and Evaluation, 2022)
This study aims to produce a simulation model of multimedia products in Basic Electrical and Electronics subjects in SMK, to test the feasibility and effectiveness of multimedia with a simulation module developed for use in Basic Electrical and Electronics subjects. This study uses the Bergman & Moore development model. The feasibility test was obtained based on expert studies conducted by material experts as well as media and learning design experts. Expert review is used to see the feasibility of multimedia and improve multimedia. After the multimedia was improved, it was then tested on class X SMK students. Media and instructional design experts gave suggestions on the product to add material conclusions and the placement of learning objectives and multimedia could be used for learning after going through the revision process. Then the material expert on this multimedia stated that the material was adequate and could be used for learning. The results of the feasibility test show that the multimedia with the simulation model developed is in the very feasible category with an average value of 83.7%. The effectiveness test was carried out by giving pre-test and post-test to class X SMK students with analysis using the N-Gain formula. The results of the effectiveness test showed that the average score of students before using multimedia was 51.33 and after using multimedia was 78.67. Based on the N-gain value of 0.59 or in percent is 59% with a fairly effective category, learning using multimedia can improve student learning outcomes.Â